2017
DOI: 10.1371/journal.pone.0174138
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-32 promotes calcification in vascular smooth muscle cells: Implications as a novel marker for coronary artery calcification

Abstract: Cardiovascular calcification is one of the most severe outcomes associated with cardiovascular disease and often results in significant morbidity and mortality. Previous reports indicated that epigenomic regulation of microRNAs (miRNAs) might play important roles in vascular smooth muscle cell (VSMC) calcification. Here, we identified potential key miRNAs involved in vascular calcification in vivo and investigated the role of miR-32-5p (miR-32). According to microarray analysis, we observed increased expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 50 publications
2
59
0
1
Order By: Relevance
“…Furthermore, the expression examination results revealed a significant increase in the expression of miR-32-5p in patients with AMI compared with healthy controls. It is reported that miR-32-5p may serve a critical role in the progression of atherosclerosis by regulating arterial calcification [17,29]. In this study, the AI values of AMI patients were significantly high, and we found that the serum levels of miR-32-5p was positively correlated with the AI values, indicating that miR-32-5p might be involved in the development of AMI by regulating the arterial calcification.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Furthermore, the expression examination results revealed a significant increase in the expression of miR-32-5p in patients with AMI compared with healthy controls. It is reported that miR-32-5p may serve a critical role in the progression of atherosclerosis by regulating arterial calcification [17,29]. In this study, the AI values of AMI patients were significantly high, and we found that the serum levels of miR-32-5p was positively correlated with the AI values, indicating that miR-32-5p might be involved in the development of AMI by regulating the arterial calcification.…”
Section: Discussionsupporting
confidence: 57%
“…The aberrant expression of miRNAs has been determined as diagnostic biomarkers or therapeutic targets in the progression of AMI [16]. miR-32-5p has been reported to modulate the viability of vascular smooth muscle cells and play as a biomarker of coronary artery calcification [17]. In addition, the regulatory effect of miR-32-5p on inflammatory responses has been found in macrophages infected by Mycobacterium tuberculosis [18] and rats with neuropathic pain [19].…”
Section: Introductionmentioning
confidence: 99%
“…And such procession is mirrored by expression of osteogenic transcription factors such as Runx2 and loss of contractile phenotype such as α‐smooth muscle actin (α‐SMA) . It is revealed that some miRs with elevated expression during VC promote osteogenesis via targeting at anti‐calcification proteins or contractile markers, whereas some other miRs with decreased expression suppress osteogenesis of VSMCs through targeting at osteogenic transcription factors (shown in Table ). As described, some of such miRs, including miR‐133b, miR‐204, miR‐211, alter during VC and are also proven to be transported by exosomes to modulate the biological behaviour in various kinds of recipient cells .…”
Section: Exosomes Participate In Vcmentioning
confidence: 99%
“…lcnRNAs have a transcript length of >200 nucleotides and were considered to have no biological function (5). However, more recent research indicates that lncRNAs participate in multiple important regulatory processes, including genome blotting, chromatin modification, transcriptional activation, transcriptional interference and intranuclear transportation (6).…”
Section: Introductionmentioning
confidence: 99%
“…An in vitro experiment indicated that HOTAIR regulates HOXD10 and HOXC11, and that HOTTIP regulates the transcription of HOXA13 (10). Certain studies demonstrate that HOTAIR is abnormally expressed in breast, pancreatic, colon and liver cancer (5,11).…”
Section: Introductionmentioning
confidence: 99%